Penyuluhan Kesehatan Tentang Corona Virus Disease 2019 (Covid-19) kepada Masyarakat di Kelurahan Losung Kecamatan Padangsidimpuan Selatan Kota Padangsidimpuan Tahun 2021 - Ramadhini, Delfi (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2021)
Covid 19 is a virus caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. COVID-19 can cause respiratory system disorders, from mild symptoms such as flu to lung infections, such as pneumonia. COVID-19 (coronavirus disease 2019) is a new type of disease caused by a virus from the coronavirus class, namely SARS-CoV -2 which is also often called the Corona virus. The purpose of this PKM is to motivate the people in Losung Village, Padangsidimpuan Selatan District about the importance of knowing about Covid-19. PKM activities are carried out by the method of health education using a powerpoint slide show media to the total number of people in Losung Village, Padangsidimpuan Selatan District. The results of this counseling activity were continued by providing an evaluation to the community in Losung Village, Padangsidimpuan Selatan District, namely questions and answers about the material given. There were several questions given by the extension agents to the community in Losung Village, Padangsidimpuan Selatan District. Based on the answers given, it shows that the people in Losung Village, South Padangsidimpuan District understand the material provided by the extension agent. PKM activities carried out went well. The community in Losung Village, Padangsidimpuan Selatan District who participated in the activity seemed enthusiastic about participating in the counseling activity. The result of this activity is to increase public knowledge, educate the public about Covid 19.